2007
DOI: 10.1097/01.ccm.0000262387.37554.2e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lower limb compression devices on thermodilution cardiac output measurement*

Abstract: Thermodilution cardiac output measurements via a pulmonary artery catheter should not be done during the inflation cycle of lower limb SCDs because they produce a falsely low cardiac output.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Less invasive methods are being used more often at the bedside to assess the patient's hemodynamics and avoid inherited risks, complications and some limitations associated with the invasive methods [3,12,13]. A pre-requisite of any method of monitoring is its accuracy, reproducibility and ease of use [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less invasive methods are being used more often at the bedside to assess the patient's hemodynamics and avoid inherited risks, complications and some limitations associated with the invasive methods [3,12,13]. A pre-requisite of any method of monitoring is its accuracy, reproducibility and ease of use [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1970s, we were introduced to the PA catheter. Its use has been in decline over the last 20 years, due to inherited risks of invasive procedures and limitations [1][2][3]. Newer less invasive methods are becoming available, such as the arterial waveform PCA, which has become very common in many ICUs across the globe.…”
Section: Introductionmentioning
confidence: 99%
“…The 65% to 100% incidence of severe thrombosis reported by Hoar et al appeared to support that logic. 2 Alternatively, one could conclude that the thrombosis observed by Hoar et al was partially the result of non-heparinbonded catheters. Although the protection conferred by heparin coating was not observed by Mollenholt et al 48 hours after placement, its use makes intuitive sense, and our recent experience with non-heparin-bonded catheters in the operating room advocates for its utility in the immediate postplacement period.…”
Section: To the Editormentioning
confidence: 97%
“…It is, perhaps, not surprising that MCDs are the most likely source of these observed tCCO observations. Previous studies in patients with bolus thermodilution cardiac output monitoring have demonstrated that inflation of lower limb MCDs decrease pulmonary artery (PA) temperature by 0.14 o C to 0.2 o C. 1,2 This phenomenon appears to occur due to a central "bolus" of cool blood from the lower extremity causing a transient but significant decrease in the PA blood temperature and an increase in the area under the thermodilution washout curve with a resulting low CO measurement. In application of this observed principle, Akinci and colleagues demonstrated in 2007 that these PA temperature variations appeared to be dependent on the timing between the MCD inflation and the cold saline bolus injection.…”
Section: To the Editormentioning
confidence: 99%
“…30 Lower limb compression devices, ubiquitous in the ICU, have even been shown to confound thermodilution cardiac output measurement. 31 Low basal blood temperature, for example, during therapeutic hypothermia, may also introduce error in measured cardiac output by the thermodilution technique.…”
Section: Cardiac Outputmentioning
confidence: 99%